Successful Application of an Insole with a Metatarsal Inhibition Bar and Deep Heel Cup for Improving Gait Dysfunction in a Patient with Poor Coordination with Disrupted Corticoreticular Tracts: A Case Report - Su Min Son; Jung Won Lee; Min Cheol Chang (MDPI AG, 2021)
We report the successful management of gait dysfunction in a patient with coordination problems using an insole with a metatarsal inhibition bar (MIB) and a deep heel cup. Furthermore, we investigated the state of the neural tracts via diffusion tensor tractography (DTT). A 23-month-old boy with gait dysfunction presented with toe walking with a wide base and decreased hip flexion. Motor weakness or spasticity was not observed. Conventional brain magnetic resonance imaging did not reveal any abnormal findings, but DTT revealed disrupted bilateral corticoreticulospinal tracts (CRTs). No abnormalities were observed in the corticospinal tract or the medial lemniscus. We applied a custom-made insole with an MIB and a deep heel cup. Immediately after application, the patient's gait pattern stabilized significantly and was nearly normalized. Our therapeutic experience indicates that the application of an insole with an MIB and deep heel cups could be beneficial for patients with coordination problems and gait dysfunction. Our DTT results showed that CRTs could be the causative brain pathology for gait dysfunction in patients with coordination problems.